Metabolic Profile, Bioactivities, and Variations in the Chemical Constituents of Essential Oils of the Ferula Genus (Apiaceae) - Sonigra, Priyankaraj; Meena, Mukesh (Frontiers in Pharmacology, 2021)
The genus Ferula is the third largest and a well-known genus of the Apiaceae family. It is categorized in the Peucedaneae tribe and Ferulinae subtribe of the Apiaceae family. At present, about 180 Ferula species have been reported. The genus is mainly distributed throughout central and South-West Asia (especially Iran and Afghanistan), the far-East, North India, and the Mediterranean. The genus Ferula is characterized by the presence of oleo-gum-resins (asafoetida, sagapenum, galbanum, and ammoniacum) and their use in natural and conventional pharmaceuticals. The main phytochemicals present in the genus Ferula are as follows: coumarin, coumarin esters, sesquiterpenes, sesquiterpene lactones, monoterpene, monoterpene coumarins, prenylated coumarins, sulfur-containing compounds, phytoestrogen, flavonoids and carbohydrates. This genus is considered to be a valuable group of medicinal plants due to its many different biological and pharmacological uses as volatile oils (essential oils). Numerous biological activities are shown by the chemical components of the essential oils obtained from different Ferula species. Because this genus includes many bioactivities such as antimicrobial, insecticidal, antioxidant, cytotoxic, etc., researchers are now focusing on this genus. Several reviews are already available on this particular genus, including information about the importance and the uses of all the phytochemicals found in the species of Ferula. Despite this, no review that specifically provides information about the biological activities of Ferula-derived essential oils, has been published yet. Therefore, the present review has been conducted to provide important information about the chemical profile, factors affecting the chemical composition, and biological activities of essential oils of the Ferula species.